Rhabdomyolysis with concurrent atorvastatin and diltiazem - Lewin, 3rd, John J; Nappi, Jean M; Taylor, Marian H (The Annals of pharmacotherapy, 2002)
To report a case of rhabdomyolysis and acute hepatitis associated with the coadministration of atorvastatin and diltiazem. A 60-year-old African American man with a significant past medical history presented to the emergency department with acute renal failure secondary to rhabdomyolysis. In addition, liver enzymes were elevated to greater than 3 times normal. The only change in medication was the initiation of diltiazem 3 weeks earlier for atrial fibrillation to a complicated medication regimen that included atorvastatin. Rhabdomyolysis has been reported in patients receiving hydroxymethylglutaryl coenzyme A (HMG-CoA) reductase inhibitors when coadministered with agents that may inhibit their metabolism. Atorvastatin is the most potent of this class of agents currently available and is commonly used in the treatment of hyperlipidemia. Rhabdomyolysis resulting from the drug interaction between diltiazem and other HMG-CoA reductase inhibitors has been described in the literature. However, no report has specifically associated this adverse event with atorvastatin and diltiazem. We describe a patient with a complex medication regimen who was admitted for rhabdomyolysis and accompanying acute renal failure, along with acute hepatitis, thought to be secondary to a drug interaction between atorvastatin and diltiazem. While optimizing the patient's lipid profile should be the primary factor in choosing one statin over another, the potential for drug interactions requires close attention. All patients beginning HMG-CoA reductase inhibitor therapy should be counseled regarding the signs and symptoms of muscle injury; particular attention should be paid to those patients who are taking medications that may interact.